Cerium-Containing Bioactive Glasses Promote In Vitro Lymphangiogenesis - Hanyu Xie; Sha Sha; Lingbo Lu; Geng Wu; Hongbing Jiang; Aldo R. Boccaccini; Kai Zheng; Rongyao Xu (Pharmaceutics, 2022)
The lymphatic system is crucial for the regeneration of many tissues due to its fundamental role in immune cell trafficking, protein transport, and tissue homeostasis maintenance. Strategies stimulating lymphangiogenesis can provide new therapeutic approaches for tissue repair and regeneration (e.g., chronic wound healing). Here, we explored the effects of cerium-containing mesoporous bioactive glass nanoparticles (Ce-MBGNs) on lymphangiogenesis. The results showed that the extracts of Ce-MBGNs (1, 5, or 10 wt/v%) were non-cytotoxic toward lymphatic endothelial cells (LECs), while they enhanced the proliferation of LECs. Moreover, as evidenced by the scratch wound healing and Transwell migration assays, conditioned media containing the extract of Ce-MBGNs (1 wt/v%) could enhance the migration of LECs in comparison to the blank control and the media containing vascular endothelial growth factor-C (VEGF-C, 50 ng/mL). Additionally, a tube-formation assay using LECs showed that the extract of Ce-MBGNs (1 wt/v%) promoted lymphatic vascular network formation. Western blot results suggested that Ce-MBGNs could induce lymphangiogenesis probably through the HIF-1α/VEGFR-3 pathway. Our study for the first time showed the effects of Ce-MBGNs on stimulating lymphangiogenesis in vitro, highlighting the potential of Ce-MBGNs for wound healing.